The structures of representations of the Tuvan language and Tuvan culture in the Russian-speaking picture of the world of young Tuvans - Moskvicheva, Svetlana A.; Suvandii, Nadezhda D.; Alexandrova, Oksana I. (The New Research of Tuva, 2024)
The article presents an analysis of the types of structures of representations of Tuvan language and culture in the daily lives of ethnic Tuvans. The authors identify central and peripheral elements in the structure and the degree of connectivity between them, as well as the presence of clusters of representations. The empirical part of the study was conducted at Tuvan State University in 2022 and 2024, involving more than 70 participants (ethnic Tuvans aged 18–30). The research used a comprehensive qualitative and quantitative approach to analyzing representations, including methods such as essays, questionnaires, and mathematical methods.It has been revealed that the structures of the representations of the Tuvan language and culture have several significant differences. The field “Tuvan Culture” domain is well-structured, with a clear distinction between the core, center, and periphery, and all elements are connected. Structurally and semantically, hyponymy is the leading mechanism. The field “Tuvan Language” domain is a loosely organized, atomic structure, with metaphor and attributive evaluative constructions as the leading types of semantic connections. At the same time, Tuvan language and culture are in a sense in complementary functional distribution, as one of the main functions of Tuvan is to ensure communication between generations, preserving the Tuvans as an ethnic group, while the main function of culture is to maintain horizontal ties within society, preserving the Tuvans as a social group.
Keywords: Tuvan language; Tuvan culture; Tuva; Tuvans; representation of language; representation of culture; structure of representation; social representation